Responses of ozone concentrations to the synergistic control of NOx and VOCs emissions in the Chengdu metropolitan area - Du, Xiaohui; Tang, Wei; Zhang, Zhongzhi; Chen, Junhui; Han, Li; Yu, Yang; Li, Yang; Li, Yingjie; Li, Hong; Chai, Fahe; Meng, Fan (Frontiers in Environmental Science, 2022)
Simulations of 108 emission reduction scenarios for NOx and VOCs using Comprehensive Air Quality Model with Extensions (CAMx) were conducted for eight cities in the Chengdu metropolitan area (CMA). The isopleth diagrams were drawn to explore the responses and differences of ozone (O3) concentrations to NOx and VOCs emission changes under Chengdu, CMA and Sichuan Province emission reduction scenarios. The results show that the O3-sensitive regimes of eight cities may change under different emission reduction scenarios. Under Chengdu emission reduction scenario, the Chengdu city is in the transition regime and O3 formation will shift from transition to VOC-limited when the VOCs emissions decreased by 50%, and the decreases in O3 concentrations caused by VOCs emission reductions are small. For the CMA and Sichuan Province emission reduction scenarios, all cities are NOx-limited in the baseline cases and with at least a 66% and a 77% reduction in NOx emissions, respectively, the daily maximum 8-h average O3 (MDA8) can attain the O3 standard (160 μg·m-3). Although reductions in VOCs emissions can also lessen the O3 concentration, the effectiveness is relatively small. The changes in O3 concentrations under different VOCs to NOx emission reduction ratios indicate that all cities achieve a relatively high O3 concentration decrement with low VOCs to NOx emission reduction ratios and that the decreasing O3 concentrations caused by non-local emission reductions are much higher than those achieved by local emission reductions. In addition, the decreases in O3 concentrations in Chengdu are quite close when the total NOx and VOCs emissions reduction percentages are less than 30% under the CMA and Sichuan emission reduction scenarios.